DIGITAL TRANSFORMATION OF MEDICAL EXPENSE INSURANCE: CLIENT-CENTERED APPROACHES AND INNOVATIVE SOLUTIONS - Loginova, Anastasiia (SWorld-Ger Conference proceedings, 2025)
The main trends in the digitalization of medical expense insurance and the role of client-oriented approaches in enhancing the efficiency of customer interaction have been identified. It is shown that the implementation of client-oriented digital services